(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article examines the importance and significance of the Invictus Games, an international Paralympic-style competition for military veterans with injuries sustained during military service. The author emphasizes the growing interest in using sports to rehabilitate military personnel with trauma and psychological consequences of combat. He also analyzes other military rehabilitation programs through sport in participating countries such as the United States, Canada, and Australia. Special emphasis is placed on the success of the Ukrainian team at the Invictus Games and its importance for veterans. The article also examines the psychological aspects of sports rehabilitation and the importance of emotional and political narratives in the context of these competitions. The research materials, which analyze in detail the role of sports in the rehabilitation of military veterans and their participation in international competitions, can be used in university courses on sports medicine, physical therapy, psychology, sociology, and military science. They can also be used in various publications, websites, presentations and other informational materials for the general public to raise awareness and support for veterans in rehabilitation. At the same time, the theoretical analysis of the content of the research material shows that insufficient attention is paid to the issues of rehabilitation of military veterans through sports in pedagogical research. This problem remains poorly researched in the pedagogical theory and practice of educational institutions, the lack of which can significantly affect the effectiveness of rehabilitation programs for military veterans. In conclusion, the author notes the slow development of rehabilitation programs in Ukraine and suggests ways to further improve in this area by creating appropriate infrastructure and promoting the participation of veterans in sports activities.